IMPORTANCE OF CLINICAL RISK INDEX FOR BABIES SCORE FOR PREDICTING NEONATAL MORTALITY IN NICU IN A TERTIARY CARE HOSPITAL - Najeeb, Shahzad; Hussain, Ejaz; Raza, Muhammad Ali; Sarwar, Shabana; Gillani, Saima; Afridi, Rifayat Ullah; Ali, Husnain; Khan, Imran Mahmood (Journal of Ayub Medical College Abbottabad, 2020)
Background: High mortality among premature and very low birth weight (VLBW) babies necessitates the need to formulate and use scoring systems like CRIB score to predict the mortality in this vulnerable group. Objective of the study was to determine the strength of Clinical Risk Index For Babies (CRIB) score in detecting neonatal mortality in babies presenting with very low birth weight so that timely intervention can be done. It was a cross-sectional study, conducted at NICU, Children Hospital, Pakistan Institute of Medical Sciences Islamabad (PIMS) in nine months starting from First July 2017. Methods: A total of two hundred and fifty-four (n=254) new-borns with birth weight of between 500-1500 grams and gestational age lesser than 35 weeks were included in the study. CRIB score was calculated in all neonates and its association was assessed with mortality during NICU stay. Recorded data was analysed for demographic variables. Means and standard deviation was calculated for numeric variables. Chi-square test was applied to find p-value for the correlation between the main variables. Results: 54.3% (n=138) patients were males and 45.7% (n=116) were females. Mean gestational age was 33.3 weeks±1.04 SD and mean birth weight of study population was 1129.9 grams±210.6 SD. Mean CRIB score among the study population was 6.3±3.1SD and overall mortality was found to be 54.7% (n=139). Mean CRIB score was found to be 8.27±2.1 SD among mortality group and it was 3.87±3.4 SD among new-borns who were discharged (p<0.05). Mortality was present in 4.3% (n=4) of neonates with CRIB score between 1 to 5, 87.1% (n=121) who had CRIB score between 6 to 10 and 100% (n=14) of neonates who had CRIB score level 11-15 (p<0.05), so a significantly higher percentage mortality was noted among neonates with higher CRIB scores. Conclusion: According to our study mean CRIB score is a significant predictor of neonatal mortality.